PERFECT HUMAN: HARMONY OF NATIONAL VALUES AND UNIVERSAL VIRTUES - Mufti zade, Gulchehra (International Conference on Culture & History, 2026)
This article examines the concept of the perfect human through the ideas of prominent thinkers and symbolic figures in national culture. It analyzes the ideals of spiritual and moral perfection and highlights the importance of the perfect individual in educating a harmoniously developed generation and promoting social progress.